(untitled) (Ukrainian Journal of Ophthalmology, 2024)
We report a case of the development of bilateral glaucoma after flow-diverting stent placement in the left internal carotid artery (ICA) in the projection of the aneurysm neck. The case confirms the importance of a multidisciplinary approach to the surgical treatment of patients with a supraclinoid ICA aneurysm, and may be of interest not only to ophthalmologists, but also to neurosurgeons and vascular surgeons.